Hormonal Management of Persistent Estrus in Bitches: A Report of Seven Cases - Borakhatariya , Devasee N; Ramoliya, Urvashi B; Nandaniya, Nirbhay R; Vala, Karshan B (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Seven bitches of various breeds presented at the VCC, Junagadh with the anamnesis of persistent vaginal bleeding since 30 to 45 days were included in this syudy. They were all subjected to a vaginal cytology, which showed that there were a lot of superficial cells (>80%). Given the vaginal cytological cellular profile, the presumptive diagnosis was made for the prolonged estrus, may be due to either follicular cysts or persistent anovulatory follicles. To induce ovulation or luteinization, the animals were treated with human chorionic gonadotrophin twice at 24-h intervals at a dose of 22 IU/kg body weight. After receiving an hCG injection, the vaginal bleeding in six of the treated animals decreased every day and almost ceased in five days, but in one instance, the bleeding continued. The recommendation for this bitch was an ovario-hysterectomy.